As representações sociais da morte para equipes de saúde de dois Centros de Terapia Intensiva - Carla Vieira Gomes Chaves (2014)
Nowadays, it is admitted in the contemporary Western society that death is at the same time an interdict and omnipresent fact. It invades day-to-day life both through the mass means of communication which broadcast news of violent deaths on a daily basis or in a silent way through the contact with those who are dying as it happens, for instance, in a hospital. Studies carried out approaching the topic in hospitals have identified that for health care professionals, a patients death is often perceived as professional failure. Such a feeling of failure has been identified more often in Intensive Care Units (ICTs), which are places characterized by having state-of-the-art technology of care/cure in medicine. According to the literature available on working conditions in such Centers, the death of patients also brings forth in the Intensive Care Units professionals the feeling of impotence and guilt. It also produces thoughts regarding such workers possible death and also of those who are a part of their social bonds. Thus, the knowledge of these health care workers social representations in relation to death, the general objective of this work, can be relevant to prevent such harms. It can also allow the proposal of actions that aim at a better quality in the care of dying patients and their families. To achieve this goal, 18 Intensive Care Units professionals were interviewed in a hospital located in the city of Belo Horizonte, Minas Gerais State, which only takes care of patients from the Sistema de Saúde Único (SUS), the Brazilian government-based health care system. The semi-structured script included the following themes: a) socio-demographic data; b) professional history; c) general working conditions in 11 ICUs; d) an assessment of the situations which are characteristic of the work done in ICUs in relation to patients and their families; e) meanings of death; and f) professional and emotional aspects related to death in ICUs. The data collected were analyzed using Content Analysis forming categories that try to contemplate the psychosocial aspects of interest for this investigation in their relation. It is concluded that the social representations of death are anchored in two perspectives, one being personal and the other professional. The first aims death as life in another place and the second as the enemy to be beaten.